Positive Solutions of a Nonlinear Parabolic Partial Differential Equation - Chengbo Zhai; Shunyong Li (Abstract and Applied Analysis)
We deal with the existence and uniqueness of positive solutions to a class of nonlinear parabolic partial differential equations, by using some fixed point theorems for mixed monotone operators with perturbation.